Debit and Credit Cards: Money Velocity Risks - Putra, Hari Setia; Huljannah, Mutia; Anis, Ali; Azhar, Zul (Jurnal Ekonomi & Studi Pembangunan, 2021)
Payment system innovations as the efforts to meet the people’s needs have recently risen several new non-cash-based payment instruments, such as card-based payment transactions. The upheaval of card-based non-cash transactions has indirectly shifted the role of cash in the society. This research aims to see the effect of cards as payment instruments represented by both debit and credit cards on money velocity in Indonesia within the period of 2016M1 to 2020M6 using the VECM (Vector Error Correction Model) analysis method. The research findings show that long-run card-based payment instrument has a significant effect on money circulation in Indonesia. It means that money velocity in Indonesia is not constant. Money velocity is a key concept in monetary theories and an important element for monetary analysis. Therefore, it is important for central bank to monitor and understand the money velocity trends to provide long-term benefits. The research findings are also expected to provide an additional insight to policymakers, especially central bank as monetary authority doe to the possibly occurring risks caused by the money circulation instability in economy.